Description of the last instar larva of Forcepsioneura sancta (Hagen in Selys 1860) (Odonata: Protoneuridae) - Anjos-Santos, Danielle; Pessacq, Pablo (Zootaxa, 2012)
The Neotropical genus Forcepsioneura Lencioni 1999 is composed of six described species (Garrison et al. 2010) endemic to the Brazilian Atlantic forest (Machado 2001; Garrison et al. 2010). The knowledge of the immature stages is restricted to the inclusion of the genus in two keys of Protoneuridae genera (Costa et al. 2004; Neiss & Hamada 2012) and brief comments on labium characters (Costa et al. 2004), without formal description. Here we describe the last instar larva of Forcepsioneura sancta (Hagen in Selys 1860) based on specimens collected in Rio de Janeiro State, Brazil.